AB0202 Glucocorticoids in the initial treat-to-target strategy of early rheumatoid arthritis. (12th June 2018) - Fedele, A.L.; Petricca, L.; Tolusso, B.; Alivernini, S.; Gigante, M.R.; Bosello, S.L.; Di Mario, C.; Ferraccioli, G.; Gremese, E.
Abstract : Background: As stated in the 2013 update of RA recommendations, glucocorticoids (GCs) should be used as bridging therapy for up to 6 months, ideally tapering them at earlier time points. 1 Objectives: To evaluate whether initial combination therapy with GCs and disease modifying anti-rheumatic drugs (DMARDs) influences clinical and radiological outcome in the real-life practice of a cohort of early rheumatoid arthritis (ERA) patients. Methods: A total of 367 ERA patients with less than 12 months of disease duration were enrolled in the study. ERA patients fulfilled the 2010 ACR criteria for RA and were followed according to the treat-to-target strategy. The mean follow-up (FU) was 38.2±32.8 months. At baseline, and every three months, the ACR/EULAR core data set variables were recorded. At baseline and every year, hand and foot radiographs were examined according to modified Total Sharp score (mTSS). At each visit, clinical improvement and remission were evaluated according to EULAR criteria. The achievement of CDC (28-joint Disease Activity Score using C reactive protein <2.6, Health Assessment Questionnaire<0.5 and change from baseline in mTSS ≤0.5) was assessed every year of follow-up. Results: At baseline 291 (71.9%) ERA patients started GCs at a dosage of 0.2 mg/Kg, gradually tapered and withdrawn as rapidly as clinically feasible. As expected, these patients presented higher values of acute phase reactants (p=0.001), and higher levels of disease activity scores (p<0.001) and disability index (p=0.001), compared to the 76 subjects (18.8%) who had not been prescribed GCs. Patients not treated with GCs were in higher percentages anti-citrullinated peptide antibody (ACPA) (75.0%) and IgM-rheumatoid factor (RF) (64.5%) positive, compared to subjects taking GCs (62.9%, p=0.05; 49.8%, p=0.02, respectively). There were no differences regarding age, disease duration, BMI, smoking habit and presence of erosions at onset. The mean duration of GC treatment was 7.5±7.9 months and the mean dosage during FU was <5 mg prednisone per day. During the FU, in the two groups a similar percentage of patients started a combination therapy with biological (b)-DMARDs and no differences were observed regarding radiographic progression. A higher rate of remission defined according to DAS values, 2011 ACR/EULAR criteria, and CDC criteria, was registered in patients not treated with GCs compared to subjects who required corticosteroid therapy. ERA patients that didn't manage to stop GCs at the sixth month (38.8%) had a higher BMI (p=0.04) and a lesser chance of achieving remission defined according to DAS values, 2011 ACR/EULAR criteria, and CDC criteria during follow-up. Moreover, a higher percentage of them required a combination therapy with bDMARDs during FU (p<0.0001). Conclusions: In our cohort ERA patients initially treated with GCs had higher disease activity scores at onset compared to subjects wihout GCs. The lesser chance of achieving remission and the higher rate of bDMARD therapy in ERA patients not able to stop GCs, reflect a more aggressive disease, refractory to conventional drugs. Reference: [1] Smolen JS, et al. Ann Rheum Dis2014;73:492–509. Disclosure of Interest: None declared